PENGARUH STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. NUSANTARA CARD SEMESTA MEDAN - Sri Murniati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2020)
This study aims to determine the effect of Work Stress variable (X) with Job Satisfaction variable (Y). The study was conducted at PT. Nusantara Card Semesta Medan. Data analysis uses the Simple Linear Regression equation. Then the significance test and determination test are held to find out how much influence the independent variable has on the dependent variable. R test results obtained r value of 0.799 where with a significant level of 5% (0.05) with a total sample of n = 32 people obtained rtab = 0.349, this means that rhit> rtab (0.799> 0.349) which indicates that the relationship between independent variables (X) towards the dependent variable (Y) is positive and the context is strong. T test results obtained thit = 7.281 while the value at n-2 is 30 at a significant level of 5% (0.05), is 2.042 and if thit> ttab is 7.281> 2.042, there is a significant effect between job stress on job satisfaction the employee. Determination test results obtained by the contribution of work stress on employee job satisfaction by 63.84% while the other 36.16% is influenced by other factors not examined based on the correlation above, then the hypothesis proposed in this study can be tested for truth.